AN OVERCOMING VOLTAGE DROP IN REPAIR CONDUCTOR USING ETAP SOFTWARE - Afrizal Chaniago; Solly Aryza; Hamdani (Sean Institute, 2022)
This study aims to determine the percentage drop in the network end voltage on the PU. 1 refiner, determine the effect of load breakdown and increase in conductors on the PU. 6 refiner on the improvement of the quality of the end voltage on the PU. 1 refiner, and get the results of the analysis of the voltage drop at the end of the network on the PU refiner. .1 with ETAP 12.60 software. The research method used is a simulation method for calculating voltage drop using Etap 12.60 software. The data taken in the form of data length, cross-sectional area, stress, and load distribution network. From the results of the study, it was found that the percentage of end voltage drop before uprating the conductor and breakdown load on the PU.6 refiner on the results of voltage measurements at Final Load = 24.12%, voltage at Middle Load = 18.09% and stress at Even Load = 12.06 %. There is a voltage drop at the end of the distribution system network with the lowest end voltage at the end load which is 15.1 kV and a voltage drop of 24.12% occurs. After raising the conductor and disconnecting the load on the refiner PU.6, the voltage at the final load on PU.1 in the ETAP result is 18.03 kV